The Linear Fitting Method for Model of PIN Array Receiver in Space Optical Communication - Qinggui, H. (International Journal of Optics, 2022)
We have proposed PIN array as receiver in space optical communication and adopted the double diode model, the widely accepted solar energy output theory, to study its characteristics of output current and voltage. In order to make the calculation simplified, the linear fitting method is put forward. Later, we adopt both the traditional method Newton-Raphson and the new linear fitting method to calculate the values of both maximum power and the corresponding voltage of 3 × 3 PIN array. The comparison result shows the calculated values with two methods are good consistent. It validates the feasibility of the new linear fitting method. In the next step, the experiment has been carried out. The experimental result validates the reasonability of adopting the double diode model to study PIN array. At the same time, it validates the feasibility of the new linear fitting method again.